(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information about the Faragina military unit, which was the elite part of the Caliphate’s army, based on historical sources and scientific literature. The transition of Central Asians into the Arab caliphs’ service, their rising military and political power in the caliphate’s central areas, and their role in the repression of popular movements and political disputes are all highlighted.